The effect of Cr3C2on microstructure and hardness of Cu5Al plasma sprayed coatings - Özel, Serkan; Turhan, Hüseyin (Carl Hanser Verlag, 2011)
Plasma spraying is a method mostly used to improve surface properties of materials. In this study, Cu + 5% Al/Cr3C2 powders were coated on the surface of Cu alloy by using the atmospheric plasma spraying (APS) method. The effect of Cr3C2 on microstructure and hardness was examined in four different coatings. For this aim, microstructure images of the coated layers were taken in optical microscope, their SEM, EDX and XRD analyses were performed, and their microhardness values were measured. It was observed that a lamellar structure occurred in the coatings containing Cu + 5% Al/Cr3C2. The microhardness decreased by adding of Cr3C2. The coating without Cr3C2 showed higher microhardness values than the containing Cr3C 2, and depending on the increase of Cr3C2 amount (5,10, 20 wt.%), the microhardness value increased. © Carl Hanser Verlag, München.
Auswirkung von Cr3C2 auf die Mikrostruktur und die Härte von Plasmaspritzbeschichtunqen aus Cu5Al
Keywords: Aluminum; Aluminum coatings; Coatings; Copper alloys; Hardness; Microhardness; Microstructure; Plasma jets; Plasma spraying; Atmospheric plasma spraying; Coated layers; Cu alloy; Plasma-sprayed coatings; Surface properties of materials; XRD analysis; Sprayed coatings